Protective Effects of Ethanolic Extract from Rhizome of Polygoni avicularis against Renal Fibrosis and Inflammation in a Diabetic Nephropathy Model - Yoon, Jung-Joo (Int J Mol Sci, 2021)
Progressive diabetic nephropathy (DN) in diabetes leads to major morbidity and mortality. The major pathological alterations of DN include mesangial expansion, extracellular matrix alterations, tubulointerstitial fibrosis, and glomerular sclerosis. Polygoni avicularis is widely used in traditional oriental medicine and has long been used as a diuretic, astringent, insecticide and antihypertensive. However, to the best of the authors’ knowledge, the effects of the ethanolic extract from rhizome of Polygoni avicularis (ER-PA) on DN have not yet been assessed. The present study aimed to identify the effect of ER-PA on renal dysfunction, which has been implicated in DN in human renal mesangial cells and db/db mice and investigate its mechanism of action. The in vivo experiment was performed using Polygoni avicularis-ethanol soluble fraction (ER-PA) and was administrated to db/db mice at 10 and 50 mg/kg dose. For the in vitro experiments, the human renal mesangial cells were induced by high glucose (HG, 25 mM). The ER-PA group showed significant amelioration in oral glucose tolerance, and insulin resistance index. ER-PA significantly improved the albumin excretion and markedly reduced plasma creatinine, kidney injury molecule-1 and C-reactive protein. In addition, ER-PA significantly suppressed inflammatory cytokines. Histopathologically, ER-PA attenuated glomerular expansion and tubular fibrosis in db/db mice. Furthermore, ER-PA suppressed the expression of renal fibrosis biomarkers (TGF and Collagen IV). ER-PA also reduced the NLR family pyrin domain containing 3 inflammatory factor level. These results suggest that ER-PA has a protective effect against renal dysfunction through improved insulin resistance as well as the inhibition of nephritis and fibrosis in DN.